Evaluating the Stability of Lytic and Lysogenic Bacteriophages in Various Protectants - Selcuk, Emine; Dokuz, Senanur; Ozbek, Tulin (ELSEVIER SCIENCE INC, 2024)
Phage therapy has regained value as a potential alternative and a complementary anti -infective approach to antibiotics in the fight against bacterial pathogens. Due to their host specificity, non-pathogenic nature for humans, and low production cost, phages offer an effective opportunity for utilization in healthcare, agriculture, and food preservation. Well-defined storage conditions are essential for commercialization and dissemination of phage usage. For this purpose, in our study, after the isolation and characterization of two different phages, one lytic and the other lysogenic; storage and shelf -life studies of phages were evaluated in a presence of various protectants (glycerol, sodium azide, DMSO with chloroform) and without any protectant during 8 -month period at four different temperatures. The short -time stability of the lytic P. syringae phage and lysogenic MRSA phage, which were determined by STEM analysis to belong to the Straboviridae and Siphoviridae families, respectively were also examined for the different temperatures and the pH levels ranging from 1.0 to 14.0. This study revealed the storage -model of phages that exhibit distinct lifecycles, for the first time and provided a theoretical basis for development and application of phages, has yielded valuable findings contributing to understanding of phage biology. (c) 2024 Published by Elsevier Inc. on behalf of American Pharmacists Association.
Keywords: Phage therapy; Phage storage; Lytic and lysogenic phages; Phage stability; Shelf life; TEMPERATURE; STORAGE; Pharmacology & Pharmacy; Chemistry